Business Model Canvas and Entrepreneurs: Dilemmas in Managerial Practice - Humberto Elias Garcia Lopes; Vívian Cândido Rodrigues; Ramon Silva Leite; Marlusa Gosling (BBR: Brazilian Business Review)
The literature on business models has developed under the assumption that they are tools that managers in general, and entrepreneurs in particular, use intensively to analyze information and make decisions. However, this approach has historically presented little empirical evidence about its relevance. This paper investigates this issue by assessing whether and how entrepreneurs use business models in their everyday practice. We used qualitative analysis of interviews with a group of micro and small entrepreneurs to evaluate their attitude toward one of the best-known business model frameworks on the market, the Business Model Canvas (BMC). The results indicated that these entrepreneurs tended to adopt the BMC if they believed their market was static. In more dynamic markets, they preferred to draw on their practical experience. These results highlight that entrepreneurs' perception of their firm's competitive environment is decisive in defining their attitude toward using business models as viable managerial tools.